Influence of Covid-19 Pandemic on the Management of Public Basic Schools in the Akuapem-North Municipality, Eastern Region, Ghana - Ansah, Seth Dade; Tetteh, Ruth (Advances in Social Sciences Research Journal, 2025)
The COVID-19 pandemic brought unprecedented challenges to global educational systems, necessitating adaptive strategies and resource management. This study investigated the impact of the pandemic on educational management in public basic schools within the Akuapem-North Municipality, Eastern Region, Ghana. Employing a pragmatist paradigm and sequential explanatory mixed methods design, data were collected from 87 headteachers using questionnaires and semi-structured interviews. The research identified the availability of educational resources, strategies adopted by headteachers, and their efficacy in managing teaching and learning as measures during the pandemic. Key findings indicated a predominant reliance on visual educational resources, strict adherence to COVID-19 protocols, and collaborative efforts in providing Personal Protective Equipment (PPEs). Despite the disruptions, headteachers demonstrated resilience and adaptability, leveraging available resources to ensure educational continuity. The study's implications extend to policy formulation, infrastructure development, and capacity building in emergency situations for educational stakeholders in Ghana and similar contexts globally.